Discovery of rimonabant and its potential analogues as anti-TB drug candidates - Gajbhiye, J. M.; More, Namita A.; Patil, Manoj D.; Ummanni, R.; Kotapalli, S. S.; Yogeeswari, P.; Sriram, D.; Masand, Vijay H. (Medicinal Chemistry Research, 2015)
Rimonabant and its analogues have been synthesized in moderate to good yields using a simple synthetic route. All the newly synthesized compounds were subjected to in vitro screening against M. tuberculosis and M. smegmatis. The most potent analogue JMG-14 exhibits MIC value of 3.13 compared to 3.25 and 50 A mu g/ml for ethambutol and pyrazinamide, respectively. The molecular docking reveals that pyrazole ring, number and position of halogen atoms play a crucial role in deciding interactions with MTCYP-121. These findings open up a new avenue in the search of potent anti-TB drugs with rimonabant and its novel analogue JMG-14 as lead molecules.
Keywords: Diaryl pyrazoles; H37Rv; MTCYP-121; Mycobacterium tuberculosis; Rimonabant; tuberculosis

Repurposing of old drugs: identification of novel sila analogues of rimonabant as potent antitubercular agents - Ramesh, R.; Shingare, R.; Anand, Amitesh; Veeraraghavan, S.; Viswanadha, S.; Ummanni, R.; Gokhale, R.; Reddy, D. S. (International Journal of Infectious Diseases, 2016)